IMPLEMENTASI MODEL JIGSAW BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN KEAKTIFAN SISWA MATA PEMBELAJARAN IPAS SISTEM PERNAPASAN MANUSIA DI SDN 2 SONOKULON - Aini, Rosina Nur; Nurwulandari, Ika; Purnawanto, Ahmad Teguh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This class action research aims for student activity in Natural and Social Science subjects by using a Jigsaw learning model with the help of puzzle media. This class action research was carried out at SDN 2 Sonokulon. The subjects of this study are class V students totalling 15 students. The class action research model used in this study is the Kemmis and Mc model. Taggart. Data on the results of student activity in learning Natural and Social Education in cycle I meeting 1 reached 40%, cycle I meeting 2 reached 46.7% completion and in cycle II has met the achievement criteria set with student activity cycle II meeting 1 reached 73.3%, cycle II meeting 2 reached 86.7% . The conclusion from this study is that the application of the Media Puzzle-assisted Jigsaw model in the learning of Natural and Social Sciences can increase the activity of students in class V of SDN 2 Sonokulon so that teachers can use the puzzle-assisted Jigsaw learning model as one of the alternatives to improve students in learning Natural and Social Sciences.